Isolated erector spinae plane block (ESPB) for the anesthesia of axillary fossa: A case report - Ergun Mendes (National Scientific Medical Center, 2020)
ESPB that has axial and sagittal spreads allows it to be as effective as the central blocks. Although its effectiveness on postoperative thorax analgesia has been vastly reported, the number of studies on its use in combination with other blocks for sedation purposes in the management of breast surgery anesthesia is limited. We present the anesthetic management of a patient for accessory breast tissue surgery by using ESPB block from T1. We observed that the effect of ESPB on skin incision and skin-related tissue retractions was limited while postoperative pain control was sufficiently managed by the skin infiltration with ESPB.